Sejarah Ekonomi Hijau: Mengurai Asal-Usul Dan Perkembangan Pemikiran Ekologis Dalam Ekonomi - Salong, Amjad (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2024)
This study examines the history and development of ecological thinking in economics, known as the green economy. Starting with the classical concept of resource limitations by economists such as Thomas Malthus and John Stuart Mill, the research explores the evolution of thought emphasizing the balance between economic growth and environmental sustainability. The early 20th-century conservation movement and the 1972 report "The Limits to Growth" were pivotal milestones that underscored the urgency of sustainable development models. In the 21st century, the green economy concept has been increasingly adopted by various countries and international organizations, such as the European Union with the Green Deal and initiatives in developing countries supported by international institutions. This research employs a literature review method to collect and analyze academic sources, resulting in a comprehensive synthesis of the contributions and challenges of the green economy. The study concludes that integrating ecological principles into economic policies can offer holistic solutions to global environmental and economic issues, paving the way for a more sustainable and inclusive future.